FRIENDLY CHILD ENGLISH LEARNING MATERIAL TRAINING FOR ELEMENTARY SCHOOL TEACHERS - Zulikhatin Nuroh, Ermawati; Liansari , Vevy (Journal of Social Comunity Services, 2025)
Objective: This study aims to address the challenges faced by English teachers at SDN Kedung Kendo, Candi-Sidoarjo, especially in relation to their qualifications and teaching practices. Specifically, the objective is to improve the quality of English education by developing self-teaching materials that are suitable for elementary school students, incorporating elements of Child-Friendly School (CFS) principles. Method: The research employs activity-based training for English teachers in the Primary School group, with a focus on creating engaging and suitable self-teaching materials. Teachers are guided on how to design and print these materials as textbooks. These activities are intended to enhance the teachers' ability to deliver content that caters to students' interests and learning characteristics, while also addressing the lack of media such as songs and videos. Results: The results indicate that the teachers were able to create effective teaching materials that were both engaging and aligned with the needs of their students. These materials, which combine the principles of the CFS program, have been successfully integrated into the teaching process. As a result, English lessons became more interactive and diverse, incorporating vocabulary and speaking exercises that were previously difficult to teach. Novelty: This study introduces a novel approach to overcoming the limitations of teacher qualifications and resources in rural schools. By empowering teachers to develop their own teaching materials and print them as textbooks, this approach enhances the overall learning experience, making it more aligned with the educational needs of students and the goals of the CFS program.